Industry and occupational employment projections overview and highlights, 2023-33. - Colato, Javier; Ice, Lindsey; Laycock, Sofia (Monthly Labor Review, 2024)
The Monthly Labor Review article presents industry and occupational employment projections from 2023 to 2033, with total employment expected to grow by 4.0 percent, adding 6.7 million jobs. Sectors such as healthcare, professional services, and information technology are projected to drive demand, influenced by demographic trends like an aging population. The impact of artificial intelligence, clean energy, and e-commerce on job growth is also discussed, with the transportation and warehousing sector expected to add new jobs due to the growth of online shopping. The article highlights the shift towards real-time retail, fast delivery, and warehouse automation in response to consumer demand and technological advancements.